Case Report - Severe hypospadias in 46, XY karyotype patients: is third level genetic testing always mandatory? - Romano, Giorgia; Rollo, Giovanni; Spagnol, Lorna; Mucciolo, Mafalda; Adorisio, Ottavio; Silveri, Massimiliano (Frontiers in Surgery, 2025)
We report a case of a 4-month-old infant with severe genital malformation and a 46, XY karyotype. Genetic testing revealed a variant in the NR5A1 gene, guiding a successful multistage surgical intervention. This case underscores the value of targeted genetic testing in guiding the management of severe hypospadias cases. While genetic investigation isn't routine for all severe hypospadias cases, Next Generation Sequencing (NGS) technologies have influenced the rate of correct diagnoses, reduced diagnostic delay, and helped to determine the need for focused medical care and timely treatment. Too commonly, surgeons tend to attach importance to malformation repair and disregard the genetic diagnoses, but we believe that precise genetic diagnosis improves the accuracy of DSD management in terms of prognostic predictions, the development of an individualized management plan and the determination of treatment options.